Forest fuel reduces the nitrogen load - calculations of nitrogen flows; Skogsbraensle minskar kvaevebelastningen - Beraekningar av kvaevefloeden - "Burstroem, F"; "Johansson, Jan" (1995)
Nitrogen deposition in Sweden has increased strongly during recent decades, particularly in southern Sweden. Nitrogen appears to be largely accumulated in biomass and in the soil. It is therefore desirable to check the accumulation of nitrogen in the forest. The most suitable way of doing this is to remove more nitrogen-rich biomass from the forest, i.e., increase the removal of felling residues from final fellings and cleanings. An ecological condition for intensive removal of fuel is that the ashes are returned. The critical load for nitrogen, CL(N), indicates the level of nitrogen deposition that the forest can withstand without leading to ecological changes. Today, nitrogen deposition is higher than the CL(N) in almost all of Sweden. CL(N) is calculated in such a manner that nitrogen deposition should largely be balanced by nitrogen losses through harvesting during a forest rotation. The value of CL(N) thus largely depends on how much nitrogen is removed with the harvested biomass. When both stems and felling residues are harvested, the CL(N) is about three times higher than in conventional forestry. The increase is directly related to the amount of nitrogen in the removed biofuel. Use of biofuel also causes a certain amount of nitrogen emissions. From the environmental viewpoint there is no difference between the sources of the nitrogen compounds. An analysis of the entire fuel chain shows that, compared with the amount of nitrogen removed from the forest with the fuel, about 5 % will be emitted as nitrogen oxides or ammonia during combustion, and a further ca 5 % during handling and transports. A net amount of about 90 % of biomass nitrogen is removed from the system and becomes inert nitrogen (Nsub 2). 60 refs, 3 figs, 4 tabs, 11 appendices
Keywords: "09 BIOMASS FUELS"; "54 ENVIRONMENTAL SCIENCES"; "AIR POLLUTION ABATEMENT"; "WOOD FUELS"; "NITROGEN"; "NITROGEN CYCLE"; "DEPOSITION"; "FORESTRY"; "NITROGEN OXIDES"; "ENVIRONMENTAL EFFECTS"; "EXPERIMENTAL DATA"; "RENEWABLE RESOURCES"